Extreme temperature and out-of-hospital cardiac arrest in Japan: A nationwide, retrospective, observational study - Onozuka, Daisuke; Hagihara, Akihito (The Science of the total environment, 2017)
Although several studies have estimated the effect of extreme temperatures on out-of-hospital cardiac arrest (OHCA) in a single city or region, few have investigated variations in this association on a national level in Japan. Daily data on OHCAs and weather variations were obtained from the 47 prefectures of Japan between 2005 and 2014. A time-series Poisson regression model with a distributed lag non-linear model was used to estimate the prefecture-specific effects. A multivariate meta-analysis was applied to pooled estimates on a national level. A total of 659,752 OHCA cases of presumed-cardiac origin met the inclusion criteria. The minimum morbidity percentile (MMP) was identified as the 84th percentile for temperature, ranging from 20.8°C in Hokkaido to 28.8°C in Okinawa. The overall pooled relative risk versus the MMP was 2.10 (95% CI: 1.84, 2.40) at extremely low temperatures (1st percentile) and 1.06 (95% CI: 1.01, 1.12) at extremely high temperatures (99th percentile). The effects of extremely high temperatures were acute and disappeared after a few days, while those of extremely low temperatures were also acute, but persisted for several days. The multivariate Cochran's Q test indicated no heterogeneity between prefectures (p=0.699; I2=1.0%). Extreme temperatures are associated with an increased risk of OHCA. Timely prevention strategies might reduce the risk of OHCA during extreme temperatures. Several days prevention should be also implemented for extremely low temperatures. [Display omitted] •Low as well as high temperatures show effects on OHCA.•Extremely high and low temperatures are associated with OHCA.•Heat effects were acute and disappeared after a few days.•Cold effects were also acute, but persisted for several days.•There was no spatial heterogeneity among prefectures.